QUALITY OF LIFE AND STRESS ADAPTATION MODELS IN PATIENTS WITH CHRONIC KIDNEY DISEASE: A LITERATURE REVIEW - Kiki Maria; Rondhianto Rondhianto; Suhari Suhari (UNEJ e-Proceeding, 2023)
Background: Chronic kidney disease can cause physiological and psychological stress. Adaptation to changes related to disease conditions is an essential component in managing chronic kidney disease. Failure to adapt can decrease the quality of life in patients with chronic kidney disease. This study aimed to identify the factors that affect quality of life and stress adaptation in patients with chronic kidney disease. Methods: Systematic reviews using the PRISMA protocol and the JBI Critical Appraisal Tool were used to determine eligible articles from four electronic databases (PubMed, Google Scholar, Proquest, and DOAJ). Inclusion criteria include patients with chronic kidney disease quality of life, published in Indonesian and English in the last five years (2019 - 2023). Result: 14 articles were obtained according to the criteria. Factors that affect the quality of life in patients with chronic kidney disease are age, comorbidities, socioeconomic status, income, coping, anxiety and depression, family support, and drug use. Positive self-acceptance, self-efficacy, and increased self-management skills can enhance the disease adaptation process, positively impacting patients' quality of life with chronic kidney disease. Conclusion: Patient adaptation to disease processes and management changes must be made to improve treatment outcomes. Nurses can develop nursing interventions based on appropriate stress adaptation models to increase the patient's ability to adapt to disease management to improve the results of care services and ultimately improve the quality of life of patients with chronic kidney disease.